Efektivitas penerapan metode al-miftah dalam meningkatkan kemampuan membaca kitab kuning bagi santri baru Di pondok pesantren syaichona Moh. Cholil bangkalan madura - Ahmad Mujali (STAI Syaichona Moh. Cholil Bangkalan, 2017)
Abstract: Boarding scientific developments show an increasing trend. Some development has taken place and are taking place in schools. Including one development methodology reading yellow book. There are several methodologies reading yellow book that has been present in schools. One of them is a method of reading the book of al-miftah developed by Islamic boarding school of Sidogiri. Al-miftah method is a combination of the Salaf methods combined with modern touches. One of the most prominent is the use of favorite songs of young people who arranged with lyrics payload read the book. Things are not found in other books read method. This study aims to determine the effectiveness of the methods of al-miftah in improving literacy yellow book for new students at boarding Syaichona Moh. Cholil Bangkalan. This study uses a quantitative research by presenting statistical data to answer and measure the level of effectiveness of the use of the methods of al-Miftah in the application of the Guidance Reading Yellow Book at boarding Syaichona Moh. Cholil Bangkalan. This study showed that: 1) the application of the methods of al-miftah for new students at boarding Syaichona Moh. Cholil Bangkalan is good; 2) The results of study by the method of al-miftah at boarding Syaichona Moh. Cholil is good; and 3) the application of the methods of al-miftah in improving reading skills for students new yellow book boarding School Syaichona Moh. Cholil Bangkalan have a positive impact on learning outcomes of new students. Third of these results we can conclude that the method of al-Miftah proven effective in improving literacy Yellow Book for new students at boarding Syaichona Moh. Cholil Bangkalan.